Expressions of CD274 (PD-L1) and CD47 rReceptors on the sSurface of bBlast cCells in AML pPatients - Hamad, Hala Mahdi; Shabeeb, Ziad Ahmed; Awad, Muthanna Mohammed (Iraqi Journal of Science, 2022)
Acute myeloid leukemia (AML) is a genetically heterogeneous clonal disease defined by the proliferation and accumulation of immature hematopoietic cells in the bone marrow and blood. This study aimed to evaluate the CD47 and CD274 (PD-L1) expression in Iraqi AML patients and its role in the disease and evasion of malignant cells from immune system. The study was conducted on 85 patients diagnosed with leukemia, 25 of them were excluded as they had taken chemotherapy for less than a week and because the proportion of tumor cells was less than 20%. Virtually, it was conducted on 60 patients with AML and 20 healthy individuals as a control group.  The expression of CD47 and CD274 (PD-L1) was evaluated using flow cytometry in the peripheral blood of AML samples only.  Also MMP-2 level in serum was evaluated via ELISA in both AML and control samples. The expression of CD47 and CD274 in AML patients was found to be high. Analysis of CD274 (PDL1) expression in blast populations showed a significant increase in the proportion of CD274 (PD-L1) positive blast cells in isolated peripheral blood samples (66.3050 ± 1.94522). Also, the CD47 expression on blast cells in AML was recorded as significantly high (64.9333±2.05873). For MMP-2 (ng/ml) level in serum, the mean level non-significantly increased in AML as compared to the control group (102.677±8.719; 92.191±5.161) respectively.